2015
DOI: 10.1007/s12013-015-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Inhibits Angiogenesis and Inflammation in Rat Filtration Surgery Model

Abstract: Bevacizumab can be potentially applied in filtration surgery in glaucoma patients. However, its mechanism remains unclear. In order to explore it, here, we established rat filtration surgery model and treat rat with Bevacizumab. At different time points after surgery, filtering blebs were collected and subjected to angiogenesis and inflammation genes analysis. Our results found that Bevacizumab significantly improved the outcome of filtration surgery and reduced complications (P < 0.05). Furthermore, angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“… 13 , 14 , 32 In addition, there are increases in TGFβ proteins in an experimental model of GFS. 33 We therefore used HTFs to explore the antifibrotic mechanisms of DiOHF under the stimulation of TGFβ1. DiOHF was found to attenuate the synthesis of collagen by preventing the incorporation of 3 H-proline to newly synthesized collagen under the stimulation of TGFβ1 in HTFs, suggesting that DiOHF treatment in the mice inhibits the de novo synthesis of collagen that occurs following GFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 , 32 In addition, there are increases in TGFβ proteins in an experimental model of GFS. 33 We therefore used HTFs to explore the antifibrotic mechanisms of DiOHF under the stimulation of TGFβ1. DiOHF was found to attenuate the synthesis of collagen by preventing the incorporation of 3 H-proline to newly synthesized collagen under the stimulation of TGFβ1 in HTFs, suggesting that DiOHF treatment in the mice inhibits the de novo synthesis of collagen that occurs following GFS.…”
Section: Discussionmentioning
confidence: 99%
“… 27 There have been several investigations on the potential anti-scarring effect of anti-vascular endothelial growth factor (VEGF) agents such as bevacizumab in experimental models of GFS. 33 , 40 , 41 The majority of these studies have shown that anti-VEGF agents limited postoperative scarring when given as an adjunct with either MMC 40 or 5-FU, 41 but not as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This research did not directly evaluate the survival time of the filtering bleb, a criterion used in some experimental studies, defined by a healed, flat and vascularized appearance of the bleb. Nevertheless, the clinical evaluation using the Moorfields Bleb Graduation System analyzed the extent, height and degree of vascularization at the surgery site, and the poor score of these parameters, indirectly, would point to the survival criterion.Another limitation was the small number of eyes in the final phase of the study, but this number is similar to that of previous publications12,22 .Because of the multifactorial nature of wound healing, it is likely that multiple agents, used simultaneously or sequentially, may be required foroptimal modulation. The association of MMC with triamcinolone acetate in the current results points to a synergistic action among these agents, with diffuse and broader blebs, less inflammatory infiltrate and less vascular proliferation in the intermediate stage of follow-up in this animal model.…”
mentioning
confidence: 80%
“…This may explain the slightly higher dose of bevacizumab required to inhibit angiogenesis induced by 9L (rat) cancer cells in the CAM model compared with other angiostatics. However, many articles have successfully used rodent models of angiogenesis for pre-clinical analysis of bevacizumab [ 57 , 58 ]. In addition to bevacizumab and temsirolimus, thalidomide, pazopanib and sunitinib also demonstrated significant reduction in tumor-induced NV.…”
Section: Discussionmentioning
confidence: 99%